Perceived Quality, Satisfaction, and Loyalty at the Destination Level of Cox’s Bazar, Bangladesh - Hossain, Md; Quaddus, Mohammed; Shanka, Teklehaimanot (ANZAM, 2012)
This empirical assessment was conducted in developing a comprehensive tourism destination loyalty model of Cox’s Bazar, Bangladesh. A conceptual model was developed and tested by a field study for making model context specific. In total 12 factors were used to develop the model. Then partial least square based structural equation modelling approach was used to test 22 relationships of proposed model on a sample of 602 visitors. Sixteen relationships were supported at different significant levels. It is expected that the results of this study will be supportive to improve present condition of tourism destination loyalty factors, particularly for beach based destination.